Comparison of Antioxidant Activities of Ethyl Acetate Extracts of Two Varieties of Sweet Potato Tuber [Ipomoea Batatas (L.)] Using Two Extraction Methodsomoea batatas (L.)] MENGGUNAKAN DUA METODE EKSTRAKSI - Defri Risviana; Imas Ratnasari; Hendy Suhendy (Universitas Muhammadiyah Malang, 2021)
The decrease in antioxidant activity can be caused by the destruction of antioxidant compounds due to heating. Several studies stated that there was no significant difference between the antioxidant activity of extracts from cold extraction and hot extraction. This study compares the antioxidant activity of the ethyl acetate extract of two varieties of sweet potato using two different extraction methods. Simplicia was extracted by hot extraction using reflux and cold extraction using maceration. The antioxidant activity of the extracts was tested by the DPPH method using UV-Vis spectrophotometry. There are two types of sweet potato used in this research; firstly, the outer skin of the tuber is purple, the inside is purple (UU), and, secondly, the outer skin is purple, the inside is orange (UO). The IC50 UUR (Purple-Purple Refluxed), UOR (Purple-Orange Refluxed), UUM (Purple-Purple Macerated), UOM (Purple-Orange Macerated) , and ascorbic acid values were 4.583, 4.614, 0.755, 18.142, and 2.680 g/ml; thus, the extraction method and sweet potato varieties affect the antioxidant activity of the extract. Maceration is the best method for UU, while reflux is the best method for UO.